2008
DOI: 10.1007/s11010-008-9787-4
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine suppresses LPS-induced astrocyte activation via modulating IKKs-IκBα-NF-κB signaling pathway

Abstract: Astrocyte activation has been implicated in the pathogenesis of many neurological diseases. These reactive astrocytes are capable of producing a variety of proinflammatory mediators and potentially neurotoxic compounds, such as nitric oxide (NO), tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6) and interleukin-1beta (IL-1beta). In this study, we examined the suppressive effects of Tetrandrine (TET) on astrocyte activation induced by lipopolysaccharide (LPS) in vitro. We found that TET decreased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…We found that both AST activation and cell death were abrogated by the suppression of NF-B activation or the blockade of endogenous TNF-␣ activity. In agreement with these results, TNF-␣ as well as NF-B activation have been implicated in the regulation of GFAP expression (25). Additionally, the exposure of ASTs to different death stimuli induces NF-B activation, and NF-B inhibitors blocked AST cell death (40).…”
Section: Discussionsupporting
confidence: 74%
“…We found that both AST activation and cell death were abrogated by the suppression of NF-B activation or the blockade of endogenous TNF-␣ activity. In agreement with these results, TNF-␣ as well as NF-B activation have been implicated in the regulation of GFAP expression (25). Additionally, the exposure of ASTs to different death stimuli induces NF-B activation, and NF-B inhibitors blocked AST cell death (40).…”
Section: Discussionsupporting
confidence: 74%
“…Studies have demonstrated that tetrandrine blocks Ca 2ϩ channels (5), has anti-proliferative features and possesses immunosuppressive properties (6). In addition, tetrandrine regulates many intracellular signaling events, including cell cycle arrest, MAP kinase activation, IB/NF-B signaling, and the transforming growth factor-␤ signaling pathway (4,7,8). We and other researchers have demonstrated that tetrandrine effectively induces apoptosis in cancer cells, suggesting that tetrandrine may be a promising agent for the treatment of cancer (9,10).…”
Section: Human Hepatocellular Carcinoma (Hcc)mentioning
confidence: 96%
“…So, considerable interest exists whether the evidence reviewed in this paper can bring new approaches for the prevention and management of delirium. In this regard, some agents with anti-inflammatory action were useful to reduce LPS-induced microglial/astrocyte activation, production of pro-inflammatory mediators and facilitating recovery from neurobehavioural symptoms [11,56,84,118]. Likewise, in models of experimental sepsis there is evidence that blockage of C5a, a small peptide derived from complement activation, can prevent BBB breakdown [45].…”
Section: Perspectives On Prevention and Treatment Of Deliriummentioning
confidence: 99%